Agriculture and soils of the Republic of Moldova: Assessment, findings, solutions - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper includes evaluation of agriculture, including soil resources of Moldova. Agricultural land area is continuously being extended and changing trends in production and consumption putting increasing pressure on land resources, which has a limited character. Small areas of agricultural land, the large number of landowners and their inappropriate placement involving deficiencies in the organization and sustainable management of agricultural land. Climate change intensifies soil degradation, desertification of agricultural land and lead to the vulnerability of ecosystems and habitats to adaption. Protection of farmland and environmental, economic, social, environmental and cultural functions are not achieved by determining the legal status of the soil as natural-historical body, basis of ecosystems with multiple functions, partially renewable natural resource. The current policy, legal-regulatory and institutional framework should be focused on the image of soils, constant supervision of changes in the composition of land resources, required to analyze and predict the ecological status of the land, to assess these changes, drawing up concepts, programs and implementation measures prevention of negative processes and determine the trends of these processes for the protection and rational use of land resources, their conservation and improvement.
Keywords: 330; agriculture; degradation; measures of protection; soils